Relaciones interpersonales de los funcionarios de la empresa Transporte Trasbordar S.A.S. en la ciudad de Montería: Estado y recomendaciones desde la actividad física. (2020)
Introduction: This research will talk about interpersonal relations in the working environment of a transport company in the city of Montería. The research will focus on the workplace and interpersonal relationships as a fundamental part of professional development. Objective: To determine some aspects of the interpersonal relations of the officials of the transshipment company in the city of Montería and offer recommendations for their intervention from physical activity. Methods: This research was developed, according to what Sampieri et al. (2014) under a quantitative approach because, depending on the nature of the variables, it is of numerical origin and statistical analysis is essential for this research. It has a descriptive scope because the phenomenon studied is disclosed. The population under study was 10 officials from the company Transport Transfer S.A.S. 10 subjects were evaluated; 5 men and 5 women aged between 28 and 40 years. Results: In graphs 1 and 2, teamwork, communication and work among colleagues are the least favorable aspects of interpersonal relationships, which has significantly impaired the productivity of the population under study and Conclusions: The aspects of Interpersonal relationships, such as teamwork, communication and the relationship between colleagues, are the criteria that are in the worst conditions and have generated inconveniences in individual performance in this study population.